Fora da caridade não há salvação: um ensaio sobre prestações altruístas no espiritismo e para além dele - Santos Barbosa, Allan Wine (2023)
This thesis proposes to discuss the importance of the notion of charity for Kardecist spiritism. Based on ethnographic material collected in a spiritist center in São Carlos, in the interior of São Paulo, it is argued that charity constitutes the encompassing value of the spiritist ideological system. Its implications for the day-to-day activities of the spiritist center and its visitors are discussed, as well as its centrality in soteriology and its relationship with concepts that are also fundamental for the religion, such as hierarchy, evolution, and mediumship. From this debate, we also seek to propose a broader analysis of the theme of charity from the bibliography of economic anthropology, carrying out this effort through the ethnographic problem that the notion of reciprocity poses for an ideal of disinterested charity, such as Kardecism conceives it. This proposal takes the debate, in the second half of the thesis, to historiographical incursions on some historical processes that marked key moments in the elaboration of the idea of charity as pure gift. Finally, it is also argued that a reflection on charity can promote new perspectives on fundamental notions and values of Western modernity, such as its notions of society, justice and its institutional arrangement for the care and control of the poor and underprivileged.